Identity Politics and the Literary Canon: Sándor Márai’s Place in the Hungarian Literary Canon - Garbacik-Balakowicz, Magdalena (Colloquia, 2024)
The paper examines the place of Sándor Márai (1900–1989) in the Hungarian literary canon, specifically, in the context of the discussion on the canon and national identity in the former Eastern Bloc countries after 1989. It draws on the understanding of the canon as a tool used to propagate a certain model of identity within a given society and shows how Márai’s work has been used in socio-political debates at different periods of his career and posthumously. The paper offers a historical perspective and analyses the different stages of Márai’s career: the path to recognition by critics and readers in the 1930s and 1940s, the period of the communist anti-Márai campaign, the period of exclusion from the literary canon, and the great comeback in the 1990s. The paper points to the main aspects that have affected Márai’s reception, and outlines the reasons behind the objections to his oeuvre. The analysis indicates the social, political and historical contexts that affect the different (re)interpretations of Márai’s work and his place in the canon. The paper concludes that, despite the writer’s posthumous literary comeback and international success, his place in the Hungarian literary canon has not been established yet; therefore, it is necessary to take a fresh approach to his work.
Keywords: Sándor Márai; Hungarian literary canon; canon revision; identity and politics